Studi Tentang Perilaku Pembelian Rumah Tipe 36 di Kabupaten Sidoarjo yang Ditinjau dari Faktor Harga, Lokasi dan Promosi - Putra, Arif Rachman; Arifin, Samsul; Jahroni, Jahroni; Munir, Misbachul; Darmawan, Didit; Rahayu Mardikaningsih; Sinambela, Ella Anastasya (Pusat Riset dan Inovasi Nasional, 2022)
. An appropriate marketing strategy is definitely needed by companies from small to large scale, there are no companies engaged in the property sector. This is because currently there are many similar property businesses with their respective attractiveness and advantages in the minds of the people. This study focuses on factors such as price, location and promotion. The method in this study is descriptive associative, namely analyzing the data by describing the data and knowing the relationship between variables. The research location is in Sidoarjo Regency. Samples were taken by accidential technique. There are 100 respondents involved in this study. Regression analysis for analysis uses SPSS version 26. This study proves that purchasing behavior is significantly affected by price partially. Location has a significant role in buying behavior. The role of promotion can significantly influence buying behavior. Likewise, buying behavior is influenced by price, location and promotion simultaneously.